A Study on Legal Policy of Pharmacy Education and Pharmacy Workers Related to the Urgency of Establishing Pharmacy Law - Pratita, Rasta Naya; Bachtiar, Adang (UI Scholars Hub, 2021)
According to the 1945 Constitution of the Republic of Indonesia, health is one of the basic human rights. One of the aspects that support health is the aspect of pharmacy. Pharmacy workers consist of Pharmacists and Pharmacy Technical Workers according to Law No. 36/2014 regarding Health Workers. In practice, pharmacy education in Indonesia is considered not sufficient to prepare the pharmacy workforce. There are currently contradictions in the applied pharmaceutical policy, where the number of pharmacy undergraduate programs is 279, while the number of pharmacist study programs is only 45. This results in an imbalance of graduates. There is a tendency that most pharmaceutical graduates will continue their professional education to become a pharmacist so that he can have full authority and is responsible for pharmaceutical work. Differences in curriculum background and type of education will lead to confusion regarding competency assessment. At the Pharmacist education level, there is no nationally applicable curriculum until this date. The difference in curriculum causes variations in the knowledge and abilities of graduates. The method used in this study is a review of articles from various legal rules related to pharmaceutical education in Indonesia. The results of this study indicate a need for synchronization of the pharmaceutical policy into one legal aspect so that there is no disharmony among the applied legal regulations. Eventually synergistic legal regulations will emerge, from education to legal certainty for Pharmacist as health professionals.